Sea buckthorn, its bioactive constituents, and mechanism of action: potential application in female reproduction - Mihal, Michal; Roychoudhury, Shubhadeep; Sirotkin, Alexander V.; Kolesarova, Adriana (Frontiers in Endocrinology, 2023)
Sea buckthorn (Hippophae rhamnoides L.) is a flowering shrub, and its berries have been utilized for decades as a raw ingredient in cuisines and herbal remedies. This evidence-based study focuses on its key bioactive constituents, and mechanism of protective effects with a focus on female reproductive processes. Parts of the plant contain phenols, carotenoids (lycopene, carotene, lutein, and zeaxanthin), flavonoids (isorhamnetin, quercetin, glycosides, and kaempferol), tocopherols, sterols, polyunsaturated fatty acids, minerals, vitamins, omega 3, 6, 9 and rare omega 7 fatty acids etc. Key polyphenolic flavonoids such as isorhamnetin and quercetin are believed to mainly responsible behind its health benefits (against cardiovascular diseases, metabolic syndrome, obesity etc.) through properties including anti-cancer, antioxidant, and anti-inflammatory activities. These sea buckthorn constituents appear to mediate healthy ovarian cell proliferation, death, and hormone release, as well as decrease ovarian cancer possibly through apoptosis, and hormonal (estrogen) release. Thus, sea buckthorn and its bioactive ingredients may have potential in the management of gynecological problems such as uterine inflammation, endometriosis, and easing symptoms of vulvovaginal atrophy in postmenopausal women (by targeting inflammatory cytokines and vascular endothelial growth factor – VEGF). Apigenin, myricetin, and luteolin have also been recommended as prospective ovarian cancer preventative and adjuvant therapy options as they can inhibit ovarian cancerogenesis by triggering apoptosis and halting the cell cycle in ovarian tumors. Furthermore, its oil (containing carotenoid, sterol, and hypericin) has been speculated as an alternative to estrogen replacement therapy for postmenopausal women particularly to improve vaginal epithelial integrity. However, it is uncertain whether steroid hormone receptors, reactive oxygen species (ROS), and inflammatory regulators are actually behind sea buckhorn’s actions. Sea buckthorn, and its compounds' health promoting potential warrants further validation not just in vitro and in animal research, but also in clinical trials to identify and/or standardize optimal methods of delivery of biologically active molecules.